2021
DOI: 10.3390/e23101346
|View full text |Cite
|
Sign up to set email alerts
|

A Network Theory Approach to Curriculum Design

Abstract: In this paper we hypothesize that education, especially at the scale of curriculum, should be treated as a complex system composed of different ideas and concepts which are inherently connected. Therefore, the task of a good teacher lies in elucidating these connections and helping students make their own connections. Such a pedagogy allows students to personalize learning and strive to be ‘creative’ and make meaning out of old ideas. The novel contribution of this work lies in the mathematical approach we und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…The Precalculus: Pathways to Calculus curriculum (Carlson et al, 2021) was developed and refined based on research on the understandings and reasoning abilities students need to succeed in calculus (Carlson et al, 2002;Carlson et al, 2010). Studies have shown that Pathways can support students in making connections between precalculus concepts (O'Meara & Vaidya, 2021) and have linked the Pathways curriculum to students' improved covariational reasoning, conceptual learning of precalculus concepts, and subsequent success in calculus (Carlson et al, 2003;McNicholl et al, 2021;Moore & Carlson, 2012). Pathways was designed to assist precalculus instructors in surfacing and advancing student thinking through rich problem-solving experiences that help students to make mathematical connections across concepts, functional representations, and to real-world contexts (Carlson et al, 2021).…”
Section: The Pathways Curriculummentioning
confidence: 99%
“…The Precalculus: Pathways to Calculus curriculum (Carlson et al, 2021) was developed and refined based on research on the understandings and reasoning abilities students need to succeed in calculus (Carlson et al, 2002;Carlson et al, 2010). Studies have shown that Pathways can support students in making connections between precalculus concepts (O'Meara & Vaidya, 2021) and have linked the Pathways curriculum to students' improved covariational reasoning, conceptual learning of precalculus concepts, and subsequent success in calculus (Carlson et al, 2003;McNicholl et al, 2021;Moore & Carlson, 2012). Pathways was designed to assist precalculus instructors in surfacing and advancing student thinking through rich problem-solving experiences that help students to make mathematical connections across concepts, functional representations, and to real-world contexts (Carlson et al, 2021).…”
Section: The Pathways Curriculummentioning
confidence: 99%